2008
DOI: 10.2337/db08-0083
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Lipoprotein Clearance Is Responsible for Increased Cholesterol in LDL Receptor Knockout Mice With Streptozotocin-Induced Diabetes

Abstract: OBJECTIVE-Patients with diabetes often have dyslipidemia and increased postprandial lipidmia. Induction of diabetes in LDL receptor (Ldlr Ϫ/Ϫ ) knockout mice also leads to marked dyslipidemia. The reasons for this are unclear. RESEARCH DESIGN AND METHODS-We placed LdlrϪ/Ϫ and heterozygous LDL receptor knockout (Ldlr ϩ/Ϫ ) mice on a high-cholesterol (0.15%) diet, induced diabetes with streptozotocin (STZ), and assessed reasons for differences in plasma cholesterol. RESULTS-STZ-induced diabetic LdlrϪ/Ϫ mice had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 50 publications
9
42
1
Order By: Relevance
“…To this end, we used tail-vein injection of Triton WR 1339 to block lipoprotein clearance from the circulation, and measured accumulation of serum TG and apolipoprotein B (apoB), the apoprotein required for hepatic VLDL assembly. Using similar methods, several previous studies have found that STZ treatment alone causes minimal changes in TG and apoB production (21)(22)(23). We found that hyperglycemic L-FoxO1 mice secreted significantly more TG than hyperglycemic control animals (Fig.…”
Section: Increased Vldl Secretion In Stz-treated L-foxo1supporting
confidence: 68%
“…To this end, we used tail-vein injection of Triton WR 1339 to block lipoprotein clearance from the circulation, and measured accumulation of serum TG and apolipoprotein B (apoB), the apoprotein required for hepatic VLDL assembly. Using similar methods, several previous studies have found that STZ treatment alone causes minimal changes in TG and apoB production (21)(22)(23). We found that hyperglycemic L-FoxO1 mice secreted significantly more TG than hyperglycemic control animals (Fig.…”
Section: Increased Vldl Secretion In Stz-treated L-foxo1supporting
confidence: 68%
“…Subsequent studies suggested that reduced sulfation correlated with diminished GlcNAc Ndeacetylase activity (7,8,10,11,13,14). Although we have not measured Ndst1 expression or enzyme activity, the compositional studies demonstrate clearly that no change in sulfation occurred.…”
Section: Analysis Of Hepatocyte Syndecan-1 In Iddm Mice-mentioning
confidence: 62%
“…One of mutants lacked the enzyme N-acetylglucosamine N-deacetylase/N-sulfotransferase 1 (Ndst1), a biosynthetic enzyme that regulates the overall level of sulfation of heparan sulfate glycosaminoglycans. In vivo studies have suggested that IDDM causes reduced expression of Ndst1 (6,10,11,13,14,18), leading to the hypothesis that hypertriglyceridemia was caused by undersulfated heparan sulfate in the liver.In this work, we show that mice with IDDM exhibit reduced [ 35 S]sulfate incorporation into hepatic heparan sulfate. However, the reduction was caused by changes in plasma sulfate concentration after the onset of diabetes rather than any change in heparan sulfate biosynthesis.…”
mentioning
confidence: 99%
“…Thus, the regulatory link between insulin and LDL receptor levels may be effectively disrupted, which may explain the lack of diabetes-induced hypercholesterolaemia in D374Y-PCSK9 + minipigs. A reduced binding of apoB48-containing remnants to hepatic proteoglycans has been suggested to cause cholesterol accumulation in diabetic LDL-receptor-deficient mice [39], but this mechanism is probably of less relevance in pigs (or humans), where the bulk of the cholesterol is carried in apoB100-containing LDL/VLDL particles. Furthermore, diabetic hyperphagia [39,40], with an increased dietary cholesterol intake in animals fed ad libitum, has been shown to contribute to diabetic hypercholesterolaemia [41,42].…”
Section: Effect Of Diabetes On Plasma Lipidsmentioning
confidence: 99%